World Pharmacists Day 2023: pharmacy strengthening health systems / Saliha Azlan and Farhana Fakhira Ismail - Azlan, Saliha; Ismail, Farhana Fakhira (Faculty of Pharmacy, 2023)
The Faculty of Pharmacy, UiTM Puncak Alam hosted the World Pharmacists Day 2023 on the 28th of October 2023. The event was a remarkable achievement, meticulously coordinated and executed by our dedicated students, under the capable leadership of Ms. Intan Rynn Zulaikha. This event brought together students from different faculties for a day filled with informative talks, interactive sessions, and health screenings. The event that was conducted at Rafflesia Student Complex offered a range of activities designed to promote health awareness and educate the community about the role of pharmacists in healthcare.